Exploring the Aesthetic Elements of Development Communication - Uduak Imoh; Christiana Chundung (International Journal of Economics, Business Management and Accounting (IJEBMA), 2019)
Development communication plays a vital role in fostering social change and facilitating sustainable development. While effective communication strategies are essential, the integration of aesthetic elements adds depth and power to development messages, resulting in increased engagement and impact. This paper examined the world of aesthetics within development communication, analyzing how visual, auditory, and sensory elements can effectively convey messages, elicit emotions, and inspire action. However, the role of aesthetics in this field has received limited attention. Findings from this research will contribute to a deeper understanding of the aesthetic dimensions of development communication, providing valuable insights for practitioners and policymakers in designing more impactful and engaging communication strategies to address pressing developmental challenges